Synthesis of Notoamide J: A Potentially Pivotal Intermediate in the Biosynthesis of Several Prenylated Indole Alkaloids - Finefield, Jennifer M. (2010)
An efficient total synthesis of notoamide J, a new prenylated indole alkaloid and potential biosynthetic precursor, is described herein. Starting from L-proline and a substituted tryptophan derivative, this synthesis also employs an oxidation and pinacol rearrangment for the formation of the oxindole in the final step.